Absolute Perfusion Measurements and Associated Iodinated Contrast Agent Time Course in Brain Metastasis: A Study for Contrast-Enhanced Radiotherapy. Issue 4 (April 2014) - Obeid, Layal; Deman, Pierre; Tessier, Alexandre; Balosso, Jacques; Estève, François; Adam, Jean- François
Contrast-enhanced radiotherapy is an innovative treatment that combines the selective accumulation of heavy elements in tumors with stereotactic irradiations using medium energy X-rays. The radiation dose enhancement depends on the absolute amount of iodine reached in the tumor and its time course. Quantitative, postinfusion iodine biodistribution and associated brain perfusion parameters were studied in human brain metastasis as key parameters for treatment feasibility and quality. Twelve patients received an intravenous bolus of iodinated contrast agent (CA) (40 mL, 4 mL/s), followed by a steady-state infusion (160 mL, 0.5 mL/s) to ensure stable intratumoral amounts of iodine during the treatment. Absolute iodine concentrations and quantitative perfusion maps were derived from 40 multislice dynamic computed tomography (CT) images of the brain. The postinfusion mean intratumoral iodine concentration (over 30 minutes) reached 1.94±0.12 mg/mL. Reasonable correlations were obtained between these concentrations and the permeability surface area product and the cerebral blood volume. To our knowledge, this is the first quantitative study of CA biodistribution versus time in brain metastasis. The study shows that suitable and stable amounts of iodine can be reached for contrast-enhanced radiotherapy. Moreover, the associated perfusion measurements provide useful information for the patient recruitment and management processes.